Effect of Selenium-Yeast supplementation on gut microbiome, intestinal histomorphology and immunity in broilers - Md. Mofijul Islam; Partha Das; Indranil Samanta; Barun Roy; Ayan Mukherjee; Tousif Mondal (The Microbe, 2024)
Selenium-yeast was mixed with the basal diet of treatment groups of birds at the dose rate of 0.15 mg/kg diet in treatment-I (T-I), 0.225 mg/kg in treatment-II (T-II) and 0.30 mg/kg in treatment-III (T-III) group. The body weight and weekly weight gain increased and, feed conversion ratio improved significantly (p<0.05) in the T-III group as compared to control group. The number of goblet cells, lymphatic nodules in the intestine was more in treated birds. The villi height and crypts depth and their ratio were significantly highest in T-III group. Bursal morphology significantly improved and the number of Hassall’s corpuscle, macrophages and plasma cells were more frequent in treated birds. Among the lymphoglandular organs, the maximum IL-10 positive cells were found in the caecum and Bursa of Fabricius (BF). Among the groups, T-III group showed weak to nil IL-10 reaction. When compared between the days, BF and spleen showed better IL-10 positive reaction on 7th day but in caecal tonsil and thymus, the better reaction was on 35th day. The expression of IL-10 in the lymphoglandular organs was significantly (p<0.05) lower and T-III had minimum expression. T-II and T-III groups were better than T-I and control groups for enhancing humoral immunity against Newcastle disease virus, reduction of gut Escherichia coli, Salmonella and increased gut Bifidobacterium spp. In conclusion, supplementation of Se-yeast to the poultry diet at the dose rate 0.30 mg/kg improved the growth performance and guts microbial health, and enhanced the immunity of poultry birds.